Efektivitas Model Inquiry Berbasis Etnosains Terhadap Pemahaman Konsep IPA di Sekolah Dasar - Imel Amelia Putri; Budi Febriyanto; Mahpudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of the ethnoscience-based inquiry learning model on elementary school students' understanding of science concepts in the topic of Harmony in Ecosystems (Eating and Being Eaten). The study was conducted in fifth-grade students at SDN Kadipaten VIII Majalengka using a quasi-experimental method and a Nonequivalent Control Group design. Subjects were divided into two groups: the experimental class, which received instruction using the ethnoscience-based inquiry model, and the control class, which received instruction using the Direct Instruction model. The research instrument was a conceptual understanding test administered before and after the learning process. Data were analyzed using the Normality test, Homogenity test, Independent Samples t-Test and N-Gain calculation to determine differences in outcomes and improvements between the two groups. The results showed that the initial abilities of both classes were relatively equal, but after the treatment, there were significant differences in learning outcomes and improvements in conceptual understanding, with the experimental class showing higher results. The ethnoscience-based inquiry model has been proven to encourage students to actively observe, ask questions, conduct simple investigations, and relate learning materials to local phenomena and culture, making learning more meaningful, engaging, and effective in improving students' understanding of science concepts.